The Market for Federal Agency Securities: Is There an Optimum Size of Issue? - Silber, William L. (The Review of Economics and Statistics, 1974)
r HE increased attention in the literature devoted to the market for federal agency securities,' parallels the rapid growth in that sector of the capital market since 1966. Two studies, one by Kochin (1972)2 and the other by Peskin (1971),3 have already appeared. These studies surveyed various aspects of the agency market, such as the structure of yields in the secondary market, the characteristics of agency securities, and certain indicators of performance in the secondary market, such as volume traded, bid-ask spreads, dealer positions and price variability. This paper is addressed to a more specific aspect of the agency market, namely, the determinants of the yield on newly-issued agency securities. In order to avoid the issue of determining the overall level of interest rates we reduce the problem to determining the yield spread between newly-issued agency securities and comparable maturity Treasury securities. A comparable maturity Treasury issue is considered the best available benchmark with which to compare newly-issued agency issues.4 A key issue which receives considerable attention below is whether there exists an optimum size of issue in the agency market. In other words, we will try to isolate the size of issue which minimizes the yield spread between an agency issue and a comparable maturity Treasury security. Minimizing this yield spread is an important objective for a federal agency since this is one criterion used to judge the efficiency with which it issues its liabilities in the capital market.5